Advances in accelerometry for cardiovascular patients: a systematic review with practical recommendations. (3rd July 2020) - Vetrovsky, Tomas; Clark, Cain C.T.; Bisi, Maria Cristina; Siranec, Michal; Linhart, Ales; Tufano, James J.; Duncan, Michael J.; Belohlavek, Jan
Abstract: Aims: Accelerometers are becoming increasingly commonplace for assessing physical activity; however, their use in patients with cardiovascular diseases is relatively substandard. We aimed to systematically review the methods used for collecting and processing accelerometer data in cardiology, using the example of heart failure, and to provide practical recommendations on how to improve objective physical activity assessment in patients with cardiovascular diseases by using accelerometers. Methods and results: Four electronic databases were searched up to September 2019 for observational, interventional, and validation studies using accelerometers to assess physical activity in patients with heart failure. Study and population characteristics, details of accelerometry data collection and processing, and description of physical activity metrics were extracted from the eligible studies and synthesized. To assess the quality and completeness of accelerometer reporting, the studies were scored using 12 items on data collection and processing, such as the placement of accelerometer, days of data collected, and criteria for non‐wear of the accelerometer. In 60 eligible studies with 3500 patients (of those, 536 were heart failure with preserved ejection fraction patients), a wide variety of accelerometer brands ( n = 27) and models ( n = 46) were used, with Actigraph being the most frequent ( n = 12), followed by Fitbit ( n = 5). The accelerometer was usually worn on the hip ( n = 32), and the most prevalent wear period was 7 days ( n = 22). The median wear time required for a valid day was 600 min, and between two and five valid days was required for a patient to be included in the analysis. The most common measures of physical activity were steps ( n = 20), activity counts ( n = 15), and time spent in moderate‐to‐vigorous physical activity ( n = 14). Only three studies validated accelerometers in a heart failure population, showing that their accuracy deteriorates at slower speeds. Studies failed to report between one and six (median 4) of the 12 scored items, with non‐wear time criteria and valid day definition being the most underreported items. Conclusions: The use of accelerometers in cardiology lacks consistency and reporting on data collection, and processing methods need to be improved. Furthermore, calculating metrics based on raw acceleration and machine learning techniques is lacking, opening the opportunity for future exploration. Therefore, we encourage researchers and clinicians to improve the quality and transparency of data collection and processing by following our proposed practical recommendations for using accelerometers in patients with cardiovascular diseases, which are outlined in the article.